2015
DOI: 10.1021/acsnano.5b01179
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printing of High-Content Graphene Scaffolds for Electronic and Biomedical Applications

Abstract: The exceptional properties of graphene enable applications in electronics, optoelectronics, energy storage, and structural composites. Here we demonstrate a 3D printable graphene (3DG) composite consisting of majority graphene and minority polylactide-co-glycolide, a biocompatible elastomer, 3D-printed from a liquid ink. This ink can be utilized under ambient conditions via extrusion-based 3D printing to create graphene structures with features as small as 100 μm composed of as few as two layers (<300 μm thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
586
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 627 publications
(593 citation statements)
references
References 48 publications
7
586
0
Order By: Relevance
“…Recent innovations in soft materials processing and microfabrication can produce low-cost and flexible electronic devices. These techniques include advanced photolithography, ink-jet printing, and 3D-printing (Muth et al, 2014;Jakus et al, 2015). While useful for prototyping, many of these approaches present potential challenges in the scalable manufacturing of high-performance electronic devices such as high unit costs, poor reproducibility, and low yields (Macdonald et al, 2014).…”
Section: Transfer Printing Of Microstructures Structuresmentioning
confidence: 99%
“…Recent innovations in soft materials processing and microfabrication can produce low-cost and flexible electronic devices. These techniques include advanced photolithography, ink-jet printing, and 3D-printing (Muth et al, 2014;Jakus et al, 2015). While useful for prototyping, many of these approaches present potential challenges in the scalable manufacturing of high-performance electronic devices such as high unit costs, poor reproducibility, and low yields (Macdonald et al, 2014).…”
Section: Transfer Printing Of Microstructures Structuresmentioning
confidence: 99%
“…Favored by low cost, easy operation, and versatile bioink, various 3D printed scaffolds have been examined in vivo studies to demonstrate its capability as customized implants at medical clinics [6][7][8][9][10][11]. For example, Jakus et al showed that 3D printed graphene structure is flexible and strong enough to be easily sutured to exiting tissue for biomedical applications [11]. Stereolithography (SL) printing is one of the most popular prototyping technologies, which can fabricate multilayered 3D scaffolds through ultravioletvisible polymerization of photocurable resins.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the method is potentially profitable for both scientific research [1] and commercial manufacturing [2]. With its rapid development in recent years, 3D printing has evolved from manufacturing prototypes to building functional components in numerous fields, ranging from mechanical engineering [3] and biomedical engineering [4][5][6], to electrochemical studies [7]. For applications in various fields, developing and characterizing printable materials with desired properties are currently key areas of research and development.…”
Section: Introductionmentioning
confidence: 99%